Inventarisasi Penyakit Pada Tanaman Cabai Merah (Capsicum annum l.) di Kebun Warga Gampong Suak Raya Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Adhitya Dwi Prasetyo; Agustinur Agustinur (Universitas Teuku Umar, 2022)
Chili (Capsicum annum L.) is one of the commodities that are needed by the community. One attempt to fulfill the necessary of household chili is by planting in the garden or vacant land. The the problem with chili plants grown in the village garden of Suak Raya is disease attacks that reduce chili productivity. This research was conducted to take an inventory of diseases that attack chili plants in the village of Suak Raya. The research was conducted using the observation method and direct sampling in the field. Identification of the disease is conducted by observing all parts of the plant that show abnormal symptoms. Sampling locations were carried out in two areas of red chili plantations in the village of Suak Raya. Garden 1 with an area of 50x80 m and garden 2 with an area of 30x52 m. Based on the results of observations obtained three types of diseases that attack chili plants in the village of Suak Raya, namely Yellow leaf disease, Fusarium wilt and brown spot.